Desenvolvimento e evidências de validade do ILEF-I: Inventário de Leitura para o Ensino Fundamental I - Leal, Priscila Reis (2018)
Successful reading depends on skills such as word recognition, fluency, and comprehension. These skills are developed from school progression and formal exposure to orthographic and linguistic rules. The evaluation of these skills is fundamental so that teachers can elaborate better interventions to the needs of the students. The objective of this work was to develop and search for evidence of validity of the ILEF-I: Reading Inventory for Elementary Education I based on the Informal Reading Inventory (IRI) using the Basic Reading Inventory (BRI) framework. ILEF-I seeks to evaluate fluency,word recognition and reading comprehension of students from the 1st to 5th year of elementary school in Brazil. A total of 110 private school students participated in the study between the 1st and 5th year of Elementary School I. Instruments of listening, reading of words and pseudowords, reading of sentences and automatic naming were applied. Analysis of the performance according to the school progression between the lists of words (correctness and time) and reading of texts (errors and time) revealed adequacy of the ILEF-I instrument according to the level of difficulties of the items. Pearson's correlation analysis between lists and texts for each school year and applied cognitive tests showed that word lists present evidence of convergent validity with the test for reading single words. It is concluded, therefore, that the instrument presents results that indicate good applicability in a school context in order to provide teachers with tools to verify the level of reading presented by students.